Blue Carbon: Examining its Role in Addressing the Climate Crisis - Alih, Alwida Abdurahman; Bara, Zuraida Julhiji (Bincang Sains dan Teknologi, 2024)
Coastal ecosystems, especially mangroves and seagrass beds, play a crucial role in maintaining the balance and sustainability of coastal ecosystems. Besides being a natural bulwark against storms and ocean waves, mangroves are unique in their ability to absorb and store carbon dioxide in their biomass and mud soil. Meanwhile, seagrass beds support the sustainability of coastal ecosystems and act as sinks for substantial marine carbon. Logging or damaging these ecosystems can result in massive releases of carbon, exacerbating climate change. Therefore, the conservation and restoration of mangroves and seagrass beds through research methods and sustainable policy implementation is essential to maintain global environmental sustainability and mitigate the impacts of climate change.